(untitled) (World Economics and Finance Bulletin, 2024)
This study aimed to verify the relationship between human resource costs and operational performance, with environmental uncertainty as a modified variable of the relationship, and in light of the Fourth Industrial Revolution (4.0) and using the quantitative methodology was tested two hypotheses The study used a questionnaire, was distributed to a sample of size, (136), Categories covered by the sample Production and operations managers Planning managers Expert executives and managers of units and divisions, In the companies operating in the energy sector (oil and gas) for the southern region and using the statistical program (SPSS), the results showed a significant relationship between the cost of human resources and operational performance at the level of (0.05), as well as the existence of a significant impact of environmental uncertainty at the level of (0.05) for the relationship between the cost of human resources and operational performance, which requires the departments of companies operating within the aforementioned sector to adopt ways to confront environmental uncertainty, In a way that keeps work going on in these companies.